A comparison of effect ofo trypanosoma evansi adjuvant vaccines - E. Ryu; King Chang Shaey (Media Veteriner, 1978)
Killed Trypanosoma evansi (T. evansi) treated by phosphate buffered saline (PBS), using weanling mice for the effective immune rest, has been reported previously (4) The effect of this vaccine vas found inconstant result of its immune response. This reason is still unknown. For strength or constaney of imunizing effect, it should have considered to use adjuvants (1,2,3) in the vaccines.Although zeolite is a very powerful abserbent material but it has not applied in the production of biological products of Trypanosoma. This study describes the comparison of the effect of vaccines which were treated by PBS, zeolite, complete Freund's. ADE, potassium aluminum sulfat (PAS), and freezethawing (1,5) vaccines.